1965
DOI: 10.1063/1.1719392
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Current Electromagnet Type Hysteresis Loop Tracer for Minerals and Rocks

Abstract: Photomicrography may be readily accomplished by standard techniques. Exposure times for luminescent photography, using High Speed Ektachrome film, range from one-half second to about one minute. A cadmium sulphide cell ohm-meter combination has been used for estimating exposure times. Some light originating in the air discharge does reach the specimen; and for critical work and the best quality photography, this stray light can be largely removed by use of a gas other than air to support the discharge. This ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The variation of initial susceptibility with temperature and of Curie point (T,) were measured using the instruments described by Radhakrishnamurty and P. W. Sahasrabudhe [ 121. Hysteresis characteristics like magnetization (M,) coercivity (H,) were determined by an ac hysteresis loop tracer described in the literature [13]. Mossbauer spectra were recorded at room temperature with constant acceleration drive and multichannel analyser (MCA 38A, ECIL, India) [14].…”
Section: Methodsmentioning
confidence: 99%
“…The variation of initial susceptibility with temperature and of Curie point (T,) were measured using the instruments described by Radhakrishnamurty and P. W. Sahasrabudhe [ 121. Hysteresis characteristics like magnetization (M,) coercivity (H,) were determined by an ac hysteresis loop tracer described in the literature [13]. Mossbauer spectra were recorded at room temperature with constant acceleration drive and multichannel analyser (MCA 38A, ECIL, India) [14].…”
Section: Methodsmentioning
confidence: 99%
“…Anisotropies of susceptibility were measured using Digico equipment, and ARUN Electronics equipment similar to that described by Likhite et al [1965] was used for measuring bulk hysteresis parameters. The Digico anisotropy delineator has been calibrated against a susceptibility bridge thus avoiding problems recently brought to light by Hrouda eta!.…”
Section: Methodsmentioning
confidence: 99%
“…A component of intermediate stability, however, is often seen directed to the southwest and down (Figure 13a). Although the resolution of these three components is sometimes poor, there is often a hint of the presence of the intermediate component reflected in the orthogonal plots which suggests that at least some of the components are CRM with overlapped stability spectra [McClelland Brown, 1982]. Figure 13b is a typical example of this behavior.…”
Section: Cooya Pooya Dolerite and Spinaway Porphyrymentioning
confidence: 98%
“…Hysteresis loops were obtained using apparatus similar to the one described by Likhite et al (1965); representative curves are shown in Fig. 9d, both at -196OC (bottom trace) and at room temperature (top trace).…”
Section: Hysteresis Loopsmentioning
confidence: 99%